Optimal dose of oxytocin to improve social impairments and repetitive behaviors in autism spectrum disorders: meta-analysis and dose–response meta-analysis of randomized controlled trials - Zhang, Yingying; Zhang, Xiaolu; Huang, Linghong (Frontiers in Psychiatry, 2025)
Social impairments and repetitive behaviors are at the core symptoms of autism spectrum disorder (ASD). Intranasal administration of the neuropeptide oxytocin (OXT) is a promising treatment. However, there have been inconsistencies in the effects of OXT on social impairments and repetitive behaviors. Therefore, a comprehensive search in PubMed, the Cochrane Library, Embase, and Web of Science was conducted to gather randomized controlled trials (RCTs) on the efficacy of OXT in patients diagnosed with ASD up to June 11, 2024. The core outcomes were social impairments measured by total Social Responsiveness Scale (SRS) scores and repetitive behaviors measured by the Repetitive Behavior Scale (RBS). This meta-analysis ultimately included 12 RCTs with 498 ASD patients. In an initial analysis, intranasal OXT showed no significant effect on social impairments. For a high dose of 48 IU per day, a beneficial effect on social impairments was found. According to the dose-response meta-analysis, the results indicated that higher doses of OXT might be more effective for social impairments. Depending on repetitive behaviors, the overall analysis showed no significant effect, while the dose over 48 IU per day revealed significant results and the dose-response meta-analysis suggested that higher doses could be more effective for repetitive behaviors. Though these findings show no consistent beneficial effects, the results of the dose-response meta-analysis suggest that high doses of intranasal OXT per day may be more effective in ASD.